Frequency response function of cracked Timoshenko beam measured by a distributed piezoelectric sensor - Khiem, Nguyen Tien; Hai, Tran Thanh; Lan, Nguyen Thi; Quyet, Ho Quang; Ngoc, Ha Thanh; Kha, Pham Van (Vietnam Journal of Mechanics, 2024)
In the present report, a novel concept of frequency response function (FRF) is introduced for piezoelectric beam. First, a model of Timoshenko beam bonded with a piezoelectric layer is established and used for deriving the conventional frequency response function acknowledged as mechanical frequency response function (MERF). Then, the output charge produced in the piezoelectric layer is calculated from the MFRF and therefore obtained frequency-dependent function is called electrical frequency response function (EFRF) for the integrated beam. This concept of FRF depends only on exciting position and can be explicitly expressed through crack parameters. So that it provides a novel instrument to modal analysis and structural health monitoring of electro-mechanical systems, especially for crack detection in beams using distributed piezoelectric sensor. The sensitivity of EFRF to crack has been examined and illustrated in numerical examples for cracked Timoshenko beam.